Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025853
|View full text |Cite
|
Sign up to set email alerts
|

Community-Empowered Air Quality Monitoring System

Abstract: Developing information technology to democratize scientific knowledge and support citizen empowerment is a challenging task. In our case, a local community suffered from air pollution caused by industrial activity. The residents lacked the technological fluency to gather and curate diverse scientific data to advocate for regulatory change. We collaborated with the community in developing an air quality monitoring system which integrated heterogeneous data over a large spatial and temporal scale. The system aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 48 publications
0
63
0
Order By: Relevance
“…The results led to the development of measures to avoid exposure to this pollutant. Furthermore, the European initiatives impacted the participants' knowledge, self-efficacy, and attitudes towards NO 2 pollution; they resulted in changed or adjusted behaviour of the involved citizens towards measures to exposure and contribution to air pollution, led to a higher sense of community, stimulated discussions with policy makers, and influenced political decisions in the involved regions (Francis and Stockwell 2014, Hsu et al 2017, Kloetzer et al 2017, Zannella 2017, Van Brussel and Huyse 2018, Haklay and Eleta 2019. Other projects, such as Luftdaten (https:// luftdaten.info/), HackAir (https://platform.hackair.eu/), and senseBox (https://sensebox.de/) experiment with self-made sensor kits and data platforms to measure particulate matter (PM), a mixture of solid particles and liquids found in the air which are either emitted directly from a source, like a construction site, or are the result of chemical reactions of other pollutants, such as NO 2 .…”
Section: Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The results led to the development of measures to avoid exposure to this pollutant. Furthermore, the European initiatives impacted the participants' knowledge, self-efficacy, and attitudes towards NO 2 pollution; they resulted in changed or adjusted behaviour of the involved citizens towards measures to exposure and contribution to air pollution, led to a higher sense of community, stimulated discussions with policy makers, and influenced political decisions in the involved regions (Francis and Stockwell 2014, Hsu et al 2017, Kloetzer et al 2017, Zannella 2017, Van Brussel and Huyse 2018, Haklay and Eleta 2019. Other projects, such as Luftdaten (https:// luftdaten.info/), HackAir (https://platform.hackair.eu/), and senseBox (https://sensebox.de/) experiment with self-made sensor kits and data platforms to measure particulate matter (PM), a mixture of solid particles and liquids found in the air which are either emitted directly from a source, like a construction site, or are the result of chemical reactions of other pollutants, such as NO 2 .…”
Section: Present Researchmentioning
confidence: 99%
“…The project expected to achieve regional impacts in all three testbeds, but learned that this requires strong efforts in communication and community building (Van Brussel and Huyse 2018). In the case of ozone, the communication issue becomes highly complex as the source of pollutant is not identifiable nor addressable compared to other citizenbased air monitoring projects dealing with other pollutants (Hsu et al 2017, Kloetzer et al 2017, Van Brussel and Huyse 2018.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…The results obtained by conducting a randomized experiment on two independent communities can be misleading. Figure 1: The left image (a) shows the user interface of our prior work, a community-empowered air quality monitoring system [6]. The right image (b) shows the user interface of our other prior work, Smell Pittsburgh [7].…”
Section: Evaluating the Impact Of Interactive Systemsmentioning
confidence: 99%
“…Despite the small sample size in 5 the analysis of self-efficacy and sense of community, the survey study found that the capability of using data-driven evidence from multiple perspectives is an important reason that the communities felt more confident after interacting with the system. Our other work, Smell Pittsburgh , is a mobile application that enables residents to report 6 pollution odors and track where these odors are frequently concentrated [7]. From our previous work, we found that smell experiences were valuable in representing how local air pollution affected the living quality of communities.…”
Section: Evaluating the Impact Of Interactive Systemsmentioning
confidence: 99%
“…Air quality and its impacts on public health are critical environmental issues for residents who live near oil and gas development sites [5]. A vital step towards addressing these issues is through the collection and dissemination of convincing scientific evidence of these impacts [8,9]. However, conveying this evidence, especially with multiple types of data at a large temporal and geographic scale, requires the assistance of computational tools.…”
Section: Introduction and Related Workmentioning
confidence: 99%